Du Point Method as Tool for Financial Performance Analysis - Aryal, Rameshower; Bista, Purushotam (Journal of Kathmandu BernHardt College, 2024)
This study undertakes a comprehensive financial performance analysis of Agricultur al Development Bank Limited (ADBL) over a specified period, employing the Du Pont method. Focusing on key financial metrics such as Net Profit Margin (NPM), Total Asset Turnover Ratio (TATR), Equity Multiplier (EM), and Return on Equity (ROE), the study aims to provide a detailed examination of ADBL’s efficiency in translating revenue into profit, asset utilization, capital structure decisions, and overall profitability. By utilizing the Du Pont method, the analysis aims to break down ROE into its constituent parts, offering valuable insights into the sources of ADBL’s financial performance and shedding light on the interplay between profitability, efficiency, and financial leverage. The study adopts a case study research design with quantitative approach with ADBL as the focal point. This approach allows for an in-depth exploration of the relationships between variables that influence the financial decisions within the bank. Findings from the analysis highlight fluctuations in NPM, stable asset utilization as indicated by TATR, an increasing reliance on debt financing depicted by EM, and significant fluctuations in ROE. Correlational analysis underscores the influential role of profitability in achieving better ROE, along with a moderate negative correlation between NPM and EM. In conclusion, these insights empower stakeholders with valuable information for assessing ADBL’s financial strength, risk profiles, and strategic decision-making within the banking industry.